A review of Alocasia (Araceae: Colocasieae) for Thailand including a novel species and new species records from South-West Thailand - Boyce, P.C (Thai Journals Online, 2008)
Alocasia is a genus of in excess of 100 species of herbaceous, laticiferous, diminutive to gigantic, usually robust herbs. The genus has recently been revised for New Guinea (Hay, 1990), Australasia (Hay & Wise, 1991), West Malesia and Sulawesi (Hay, 1998), the Philippines (Hay, 1999) while post main-treatment novelties have been described for New Guinea (Hay, 1994) Borneo (Hay, Boyce & Wong, 1997; Hay, 2000; Boyce, 2007) & Sulawesi (Yuzammi & Hay, 1998). Currently the genus is least well understood in the trans-Himalaya (NE India to SW China) including the northern parts of Burma, Thailand, Lao PDR and Vietnam with only the flora of Bhutan (Noltie, 1994) partly covering this range. In the absence of extensive fieldwork the account presented here for Thailand can at best be regarded as provisional.